2012
DOI: 10.1063/1.4711103
|View full text |Cite
|
Sign up to set email alerts
|

Valence-band-ordering of a strain-free bulk ZnO single crystal identified by four-wave-mixing spectroscopy technique

Abstract: Depolarization effect on optical control of exciton states confined in GaAs thin films J. Appl. Phys. 110, 043514 (2011) Theoretical and experimental studies of surface plasmons excited at metal-uniaxial dielectric interface Appl. Phys. Lett. 98, 021113 (2011) Lateral spatial switching of excitons using vertical electric fields in semiconductor quantum rings Appl. Phys. Lett. 97, 173101 (2010) Enhanced exciton photoluminescence in the selectively Si-doped GaAs/AlxGa1−xAs heterostructures J. Appl. Phys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
13
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(14 citation statements)
references
References 51 publications
(59 reference statements)
1
13
0
Order By: Relevance
“…Nevertheless, some authors [14][15][16][17][18][19][20][21][22] have rejected this interpretation in favor of the conventional 9 − 7 − 7 ordering (i.e. so > 0).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Nevertheless, some authors [14][15][16][17][18][19][20][21][22] have rejected this interpretation in favor of the conventional 9 − 7 − 7 ordering (i.e. so > 0).…”
Section: Introductionmentioning
confidence: 99%
“…As such, we believe it is worth getting this work [28] formally published, which is mainly motivated by the very recent claim of the conventional 9 − 7 − 7 ordering by [22]. It is a matter of fact that even after the convincing experiments of [12], there are still other voices.…”
Section: Introductionmentioning
confidence: 99%
“…After that, however, Reynolds et al 11 investigated optically unallowed excitons by the mageto-optical responses, and identified the Γ 9 symmetry for the topmost valence band as well as the other wurtzite compounds. Since their work, studies identifying both Γ 7 [12][13][14] and Γ 9 [15][16][17] symmetry have been reported. From the group theory, the 1s-exciton groundstate symmetry in wurtzite-ZnO is represented as 18…”
Section: Introductionmentioning
confidence: 99%
“…17 ) without the view point of the radiation-induced component-mixing. On the other hand, the present results indicate that the coupled modes contributing the signals include both A and B exciton components comparably, which would change the conventional interpretation of the observed spectra.…”
Section: Dfwm Signalsmentioning
confidence: 99%
See 1 more Smart Citation